Different effects of anthocyanins and phenolic acids from wild blueberry (Vaccinium angustifolium) on monocytes adhesion to endothelial cells in a TNF‐α stimulated proinflammatory environment. Issue 11 (6th September 2016) - Del Bo', Cristian; Roursgaard, Martin; Porrini, Marisa; Loft, Steffen; Møller, Peter; Riso, Patrizia
Abstract : This study investigates the capacity of two different wild blueberry ( Vaccinium angustifolium ) fractions (anthocyanin‐rich‐ and phenolic‐acid‐rich fraction), single anthocyanins (malvidin, delphinidin, and cyanidin‐3‐glucoside) and metabolic products (syringic, gallic, and protocatechuic acid) to prevent monocytes adhesion to endothelial cells in a TNF‐α stimulated proinflammatory environment. The concentrations range from 0.01 μg/mL to 10 μg/mL. Abstract : Scope: Monocyte adhesion to the vascular endothelium is a crucial step in the early stages of atherogenesis. This study aims to investigate the capacity of an anthocyanin (ACN) and phenolic acid (PA) rich fraction (RF) of a wild blueberry, single ACNs (cyanidin, malvidin, delphinidin) and related metabolites (protocatechuic, syringic, and gallic acid) to counteract monocytes (THP‐1) adhesion to human umbilical vein endothelial cells (HUVECs) in a tumor necrosis factor α (TNF‐α) mediated proinflammatory environment. Methods and results: HUVECs were incubated with different concentrations (from 0.01 to 10 μg/mL) of the compounds for 24 h. Labeled monocytic THP‐1 cells were added to HUVECs and their adhesion was induced by TNF‐α (100 ng/mL). ACN‐RF reduced THP‐1 adhesion to HUVECs with a maximum effect at 10 μg/mL (−33%). PA‐RF counteracted THP‐1 adhesion at 0.01, 0.1, and 1 μg/mL (−45, −48.7, and −27.6%, respectively), but not at maximum concentration. Supplementation with gallic acid reduced THP‐1 adhesion to HUVECs with a maximum effect at 1 μg/mL (−29.9%), while malvidin‐3‐glucoside and syringic acid increased the adhesion. No effect was observed for the other compounds. Conclusion: These results suggest that ACNs/PA‐RF may prevent atherogenesis while the effects of the single ACNs and metabolites are controversial and merit further exploration.